SOSIALISASI DALAM UPAYA DAN PENANGANAN STUNTING OLEH MAHASISWA KKN DI DESA PLOSO, KECAMATAN KREMBUNG SIDOARJO - Shohebatuz Sofiyah; Rusita Rusita; Evi Dwiyanti; Setiana Andarwulan (Bajang Institute, 2023)
Ploso Village is an area located in the Krembung District, Sidoarjo Regency. This village is one of the villages that currently has problems with the nutritional status of toddlers. The nutritional status of toddlers will affect their growth and development and has the potential to cause stunting. Stunting is a condition in which a child experiences a growth disorder which will cause his height not to grow according to his potential. If this condition is not handled immediately, it can affect their future in the future. Therefore, PGRI Adi Buana Surabaya University Community Service Students provide socialization related to stunting. The purpose of this stunting socialization is to increase knowledge to the people of Ploso village about stunting and the causes of its symptoms, as well as the high risks caused by stunting. The method used is related to the delivery of information in collaboration with the village midwife which is conveyed to cadres, PKK mothers. The implementation of the early activities was carried out on December 24, 2022 with a total of 20 participants. The importance of holding socialization activities in collaboration with midwives, cadres and PKK mothers is to realize good nutritional growth and prevent stunting in toddlers specifically in Ploso Village, Krembung Sidoarjo District.